Impact of cyclooxygenase-2 over-expression on the prognosis of breast cancer patients - (:unkn) unknown (AVES, 2016)
Objective: The aim of this present study was to assess the impact of COX-2 over-expression on breast cancer survival. Material and Methods: Non-metastatic invasive breast cancer patients who received adequate loco-regional and systemic treatments were evaluated. Patients' demographic, clinical, pathologic, and treatment-related and survival data were retrieved from their hospital files. COX-2, estrogen/progesterone receptor (ER/PR), HER-2/neu expression and Ki67 index of the tumors were determined immunohistochemically. As the primary objective, COX-2 positive and negative patients were compared in terms of overall (OS), disease-free (DFS) and breast cancer-specific survival (BCSS). Secondary objectives were to assess the independent prognostic factors for survival. In addition, the correlation of COX-2 expression with conventional prognostic and predictive factors of breast cancer was assessed. Results: Two hundred and seventeen patients who underwent adequate breast cancer treatment between November 2004 and December 2013 were included in the study. The median follow-up was 37 months (range: 5-107). Eighty-one (37%) patients were COX-2 positive. OS, DFS, and BCSS were similar in COX-2 positive and negative patients. Ki67 index and age were significantly correlated with COX-2 expression (r=-0.116; p=0.02; r=0.159; p=0.02). PR expression was found to be the only independent factor for predicting OS, tumor size and molecular subtype classification were found to be the only independent factors for predicting DFS, and PR expression was found to be the only independent factor for predicting BCSS. Conclusion: Among the independent predictive and prognostic factors of breast cancer, COX-2 over-expression was only correlated with Ki67 index and age.
Keywords: Breast cancer; survival; cyclooxygenase-2 enzyme; predictive factors; prognostic factors; CARCINOMA IN-SITU; COX-2 EXPRESSION; ENDOTHELIAL-CELLS; HER-2/NEU STATUS; APOPTOSIS; CELECOXIB; SURVIVAL; OVEREXPRESSION; METASTASIS; TUMORS